Determinan Kesejahteraan Petani Subsektor Tanaman Pangan (Studi Kasus 8 Provinsi di Indonesia Tahun 2011-2020) - Azzahra, Tiara; Amalia, Fitri; Widodo, Shelby Devianty (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2023)
The agricultural sector is an important and strategic sector for the economy in Indonesia. One of the indicators/measuring tools that can be used to assess the level of welfare of farmers is the Farmer's Exchange Rate. The purpose of this study was to determine the effect of harvested area, labor productivity, road length, rainfall level and agricultural machinery on the Welfare of Farmers in the Food Crops Subsector in 8 Provinces in Indonesia. The data analysis method used in this research is logistic regression analysis with the logit method. The results of this study found that the variable road length and agricultural machinery had a negative effect on the welfare of food crop farmers in 8 provinces in Indonesia for the 2011-2020 period. While the variable harvest area, labor productivity and rainfall levels have a positive effect on Welfare of food crop farmers (NTPP).